Detecting Ureaplasma urealyticum among HIV-infected women with or without human papillomavirus using real-time PCR with the ANYPLEX™ II STI-7 assay system - Adjah, J.; Taylor, J.; Ossei, P.P.S.; Pradhan, K.; Agyeman-Duah, E.; Afranie, B.O.; Donkor, S.; Ayibor, W. (Journal of Taibah University Medical Sciences, 2019)
Objectives: Human immunodeficiency virus (HIV) infections increase the chances of women contracting human papillomavirus (HPV), the prime causative agent of cervical cancer. Additionally, Ureaplasma urealyticum is the most frequent pathogen prevailing in sexually transmitted diseases in HIV-infected women. The aim of this study was to determine the presence of U. urealyticum among HIV-infected women with or without HPV in Ghana. Methods: DNA samples were extracted from cervicovaginal swabs obtained from 96 HIV-infected women attending the Kumasi South Hospital. U. urealyticum in the DNA samples was detected by real-time PCR with the Anyplex II STI-7 detection assay. Microsoft Excel was used to analyze the data, and the Chi-square test was used to determine associations and dependence among the variables.Results: Among the study population, 93.75% (90/96) were positive for at least one pathogen.In total, 36.5% (35/96) of the women were infected by U. urealyticum, with 30.21% (29/96) being co-infected with HPV. There was no significant association (95% CI, p > 0.05) between U. urealyticum and HPV status among the HIVinfected women. Conclusion: U. urealyticum and HPV are highly pathogenic, and their prevalence in this study reiterates the need for their routine screening in HIV-infected patients.
Research Article
Keywords: Co-infection; Ghana; Human immunodeficiency virus; Human Papillomavirus; Ureaplasma urealyticum